S47. A MULTICENTER STUDY OF COGNITIVE RESERVE IN FIRST-EPISODE PYCHOSIS. (18th May 2020) - Amoretti, Silvia; Anmella, Gerard; Meseguer, Ana; Saiz, Cristina; Canals, Sonia; Contreras, Fernando; Pérez, Ferran; Garrido, Ignasi; Safont, Gemma; Pons, Maite; Mezquida, Gisela; Sagué, Maria; et al.
Abstract: Background: The cognitive reserve (CR) refers to the brain's capacity to cope with pathology in order to minimize the symptoms. In the field of first episode psychosis (FEP), the CR was able to predict functional and neurocognitive performance. Nevertheless, CR has been estimated using heterogeneous methods, which, in term, difficult to compare studies. Therefore, there is a need to create a specific scale for the assessment of this relevant construct. The Cognitive Reserve Assessment Scale in Health (CRASH) is the first measure developed specifically for patients with severe mental illness with optimal psychometric properties, facilitating reliable and valid measurement of CR. The study of the internal structure of the CRASH determined a four-factor structure (Education, Occupation, Leisure activities and Sociability) that can be analyzed separately to know what kind of relationship they might have with other variables. The aim of this study was to analyze the effects of CR measured with CRASH scale on functioning and neurocognitive performance and to explore the relationship of each factor with the outcome in an adult sample of subjects with FEP. Methods: The sample of this study came from a multicentre, naturalistic and longitudinal research project financed by a catalan grant ("Pla Estratègic de Recerca i Innovació en Salut" - PERIS 2016–2018). Expedient Nº: SLT006/17/00345; entitled "Identificación y caracterización del valor predictivo de la reserva cognitiva en el curso evolutivo y respuesta en terapéutica en personas con un primer episodio psicótico". 23 FEP patients and 72 healthy control (HC) were enrolled. The premorbid IQ was estimated with the Wechsler Adult Intelligence Scale (WAIS-IV) vocabulary subtest. To assess processing speed, Trail Making Test-part A was used. Sustained attention was tested with the Continuous Performance Test–II. The working memory was assessed with the Letters and Numbers Subtest of the WAIS-IV. Finally, the executive functions tested set shifting, planning and cognitive flexibility using the Tower of London task and the Trail Making Test (TMT) part B. Results: Significant differences between the total CRASH score of patients and HC groups have been found. The patient group obtained lower scores compared to the HC group (36.66±16.01 vs 49.83±11.08, p<0.001). After performing a logistic regression to assess the predictive power of CRASH for each group, the model correctly classified 83.2% of the cases (B=0.091; p<0.001; Exp(B)=1.095). In FEP patients, the CRASH score was associated with premorbid IQ (p<0.001), processing speed (p=0.005), executive function (TMT-B, p=0.005; London Tower task, p=0.039) and attention (CPT Hit SE ISI change, p=0.004). Specifically, the Education factor was associated with premorbid IQ, processing speed, working memory and executive function. The Occupation was only associated with executive function. Leisure activities factor was correlated with premorbid IQ and functioning. Finally, Sociability was correlated with psychosocial functioning and duration of untreated psychosis. In HC, CRASH was associated with premorbid IQ (p<0.001) and attention (p=0.015). Education and Occupation factors were associated with premorbid IQ and attention; Leisure activities with processing speed; and sociability with attention. Discussion: FEP patients were shown to have lower CR than HC, and CRASH correctly classified 83.2% of the sample. Each CRASH factor was associated with different outcome, which is why it can be interesting to analyze the total CRASH score and each factor separately. Patients with higher CR showed a better cognitive performance. Therefore, enhancing each factor involved in cognitive reserve may improve outcomes in FEP.